Innate immune activation in neutrophilic asthma and bronchiectasis - Simpson, Jodie L (BMJ Group, 2007)
BACKGROUND: The role of the innate immune system in the pathogenesis of asthma is unclear. Activation of innate immune receptors in response to bacterial lipopolysaccharide, viral infection and particulate matter triggers a pre‐programmed inflammatory response, which involves interleukin (IL)8 and neutrophil influx. The inflammatory response in asthma is heterogeneous. AIM: To test the hypothesis that innate immune activation may be a relevant inflammatory mechanism in neutrophilic asthma where IL8 levels are increased. METHODS: Induced sputum was obtained from non‐smoking adults with asthma (n = 49), healthy controls (n = 13) and a positive reference group with bronchiectasis (n = 9). Subjects with asthma were classified into inflammatory subtypes using induced sputum cell counts. Sputum was examined for mRNA expression of the innate immune receptors toll‐like receptor (TLR)2, TLR4 and CD14, and inflammatory cytokines. A separate sputum portion was dispersed and the supernatant assayed for surfactant protein A, IL8, soluble CD14 and endotoxin. RESULTS: Expression of innate immune receptors was increased in subjects with bronchiectasis and neutrophilic asthma compared with other asthma subtypes and controls. Increased expression of the receptors TLR2, TLR4 and CD14, as well as the pro‐inflammatory cytokines IL8 and IL1β, was observed. Subjects with neutrophilic asthma had higher airway levels of endotoxin than the other groups studied. CONCLUSION: There is evidence of activation of the innate immune system in asthma which results in the production of pro‐inflammatory cytokines and may contribute to the pathogenesis of neutrophilic asthma.